Analysis Of Customer Satisfaction In PT. BPR Nusamba Cash Office Wado Sumedang - Agung Akbar; Teguh Santoso; Risa Ratna Gumilang (SINTESA, 2022)
Banking is the core of every country's financial system. Through lending activities and various services provided, the Bank serves financing needs and expedited payment system mechanisms for all sectors of the economy. The problem is customer complaints at PT. BPR Nusamba Tanjungsari Cash Office Wado Sumedang. Customer complaints are caused by the lack of rapid response from employees to customers, credit services are still slow, based on this research objective is to analyze and solutions to improve customer satisfaction at PT. BPR Nusamba Tanjungsari Cash Office Wado Sumedang. The research method uses a qualitative research method approach. The sampling technique is done by accidental sampling technique. Research informants are: cash chief, wado, teller , customer service and customers of PT. BPR Nusamba Tanjungsari Cash Office Wado Sumedang. The research data were analyzed using the Miles and Huberman model with steps: data reduction, data presentation, drawing conclusions. Research variables have been analyzed, including: physical evidence, reliability, responsiveness, assurance or certainty, and empathy. The results showed the facilities at PT. BPR Nusamba Tanjungsari Cash Office Wado Sumedang that the dimensions of physical evidence (tangibles), reflected in physical facilities, lack of atm machines. Dimensions of responsiveness (responsiveness), less deft in providing services